Epidemiological Investigation of Animal Brucellosis in Domestic Ruminants in Greece from 2015 to 2022 and Genetic Characterization of Prevalent Strains - Mary Emmanouil; Dimitrios Vourvidis; Anna Kyrma; Sofia Makka; Elina Horefti; Emmanouil Angelakis (Pathogens)
Brucellosis is one of the most important zoonotic diseases in Greece, causing a significant burden on both human and animal vitality as well as economic loss. The present study was conducted from 2015 to 2022 on 711,415 serum samples by determining the seroepidemiology of Brucellosis among livestock in 24 geographical areas in Greece using the Rose Bengal Test (RBT) and the complement fixation test (CFT) and further performing genetic analysis of Brucella spp. by species-specific real-time PCR and MLVA Brucella analysis. A total of 3086 serum samples from goats, sheep, and cattle showed positive results using the RBT and CFT, and only strongly positive samples (n = 800) were preserved in the Βlood Bank of the Veterinary Laboratory of Brucellosis. From these, 212 sera samples were randomly selected for molecular and genetic analysis. The results indicated that the incidence rate of Brucellosis is higher in cattle herds in comparison with other animal species. Overall, 48 samples tested positive by real-time PCR, of which forty-seven of them were B. abortus and one was B. melitensis. Genetic analysis of two B. abortus samples revealed a common pattern, indicating two Bruce04, two Bruce18, four Bruce07, two Bruce09, three Bruce16, and four Bruce30 for both samples, which, interestingly, were not identical with the known genotypes in the public MLVA Brucella database. Our findings substantiate that animal Brucellosis remains a health issue in Greece, with a stable but apparent incidence rate, and further investigation is needed to fully characterize the newly identified Brucella strains in Greece.